Linking green space to neighborhood social capital in older adults: The role of perceived safety. (June 2018) - Hong, Andy; Sallis, James F.; King, Abby C.; Conway, Terry L.; Saelens, Brian; Cain, Kelli L.; Fox, Eric H.; Frank, Lawrence D.
Abstract: This study examines the moderating effect of perceived safety on the association of green space with neighborhood social capital in older adults. Green space may play an important role for promoting neighborhood social capital and health for older adults; however, safety remains a significant challenge in maximizing the benefits of green space. Data were drawn from 647 independent-living seniors who participated in the Senior Neighborhood Quality of Life Study in the Seattle/King County and Baltimore/Washington DC region. The results suggest that certain green space elements, such as natural sights, may be beneficial to neighborhood social capital of older adults. However, other types of green space, such as parks and street trees, may be less advantageous to older adults who perceive their neighborhoods as unsafe for pedestrians. Findings highlight the importance of pedestrian safety in examining associations of green space with neighborhood social capital in older adults. Further studies using a longitudinal design are warranted to confirm the causality of the findings. Highlights: Little is known about the role of safety in linking green space to social capital. Different types of green space had different effects on social capital. Natural sights were positively related to social capital regardless of safety. Street trees and park access were negatively related when people feel less safe.